2023
DOI: 10.1021/acsami.3c06599
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Inspired Engineered Multidomain Amphiphilic Injectable Peptide Hydrogel─An Excellent Antibacterial, Angiogenic, and Biocompatible Wound Healing Material

Abstract: The ingrained mechanical robustness of amyloids in association with their fine-tunable physicochemical properties results in the rational design and synthesis of tailor-made biomaterials for specific applications. However, the incredible antimicrobial efficacy of these ensembles has largely been overlooked. This research work provides an insight into the interplay between selfassembly and antimicrobial activity of amyloid-derived peptide amphiphiles and thereby establishes a newfangled design principle toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The resolution of wound healing is closely linked to the presence of balanced collagen deposition at the wound site. The Masson trichrome staining technique was utilized to assess the quantity of collagen that had accumulated in the surroundings of the wound . On the basis of the analysis of Figure B of the 10-day excised skin samples, it was evident that the group treated with SG-Cu-PA-NV hydrogel showed a substantial increase in collagen deposition (stained blue) on the 10th day, closely followed by the PA-NV treated sections.…”
Section: Resultsmentioning
confidence: 99%
“…The resolution of wound healing is closely linked to the presence of balanced collagen deposition at the wound site. The Masson trichrome staining technique was utilized to assess the quantity of collagen that had accumulated in the surroundings of the wound . On the basis of the analysis of Figure B of the 10-day excised skin samples, it was evident that the group treated with SG-Cu-PA-NV hydrogel showed a substantial increase in collagen deposition (stained blue) on the 10th day, closely followed by the PA-NV treated sections.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial proliferation was assessed by colony assay. 34 The images of the spread plates of F. nucleatum and S. aureus disclosed a lower bacterial count in the hydrogel groups compared to the control group, and the bactericidal effect was signicantly enhanced with increasing zinc ion concentration (p < 0.05). In the time kill assay (Fig.…”
Section: Evaluation Of the Anti-bacterial Activity Of The Oc-zn Hydro...mentioning
confidence: 94%
“…Later, the antimicrobial activity of C 16 -KKFF in a hybrid material with alginate and graphene oxide was examined, and significant antimicrobial activity specific to the Gram-positive bacterium Listeria monocytogenes was noted . Another recent study reports a very thorough investigation of the self-assembly, antibacterial, and wound-healing properties of lysine-rich lipopeptides incorporating amyloid sequences to drive β-sheet fibril formation . Laverty and co-workers developed antimicrobial lipopeptides of the form C n -OOWW ( n = 6–16, and O denotes ornithine, the analogue of lysine with one less methyl group in the side chain) .…”
Section: Introductionmentioning
confidence: 99%
“… 35 Another recent study reports a very thorough investigation of the self-assembly, antibacterial, and wound-healing properties of lysine-rich lipopeptides incorporating amyloid sequences to drive β-sheet fibril formation. 36 Laverty and co-workers developed antimicrobial lipopeptides of the form C n -OOWW ( n = 6–16, and O denotes ornithine, the analogue of lysine with one less methyl group in the side chain). 37 Most closely related to the study here, Makovitzki et al reported lipopeptides comprising palmitic acid conjugated to cationic di- and tri-peptides containing all l -amino acids or mixed d , l -sequences and observed significant antimicrobial activity, although the conjugates containing d -amino acid did not display any enhanced activity compared to those based on l -amino acids.…”
Section: Introductionmentioning
confidence: 99%